The Role Of Accounting Information Systems In Improving The Tax Accounting Process - Ahmed Kadhim Sendw (Penerbit Jurnal Indonesia, 2026)
The research aims to demonstrate the role of accounting information systems (AIS) in improving the tax assessment process, as well as to clarify the extent of their impact on this process. Sixty survey forms were distributed to study the opinions of the staff of the General Tax Authority and were statistically analyzed to test research theories. The researcher touched several deductions, the most significant being that the use of AIS by the tax administration will enhance trust between the parties involved in the tax assessment process, namely the taxpayer and the tax administration. Additionally, the relevance of accounting information helps increase the effectiveness, efficiency and diligence of assessors in ensuring the accuracy of the tax assessment process